THE INFLUENCE OF WELDING CURRENTS ON THE MECHANICAL AND PHYSICAL PROPERTIES OF CHROMIUM-MOLYBDENUM STEEL (Journal of Mechanical Engineering, 2014)
An attempt has been made to determine the strength and impact properties of Cr-Mo steel base metal and joints welded by varying the current during manual metal arc welding. A set of sample is heat treated at 650°C for 2 hours and cooled in furnace to room temperature. Microstudy of the welded Cr-Mo steels is performed to make relationship with properties. Microhardness and hardness are measured at different locations viz., base metal, heat affected zone (HAZ) and weld deposit. Toughness over a temperature range from -32 to 100°C of three zones at three current settings is measured. It is found that toughness of all three zones at -32°C is almost same for any current settings. The toughness at HAZ area are higher than that of deposited weld area due to the coarsening of ferrite grain of HAZ occurs with higher heat input. The hardness and tensile properties of three zones with different welding current is also discussed.DOI: http://dx.doi.org/10.3329/jme.v44i1.19493